2007
DOI: 10.1007/s11269-007-9227-3
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Water Main Failure Rates Using the Log-linear ROCOF and the Power Law Process

Abstract: This paper presents applications of the log-linear ROCOF and the power law process to model the failure rate and estimate the economically optimal replacement time of the individual pipes in a water distribution system. The performance of the two failure rate models is examined using the maximized log-likelihoods for different modeling approaches in which the method of observing failures differs. The optimal replacement time equations for the two models are developed by applying the methodology of Loganathan e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 15 publications
2
16
0
3
Order By: Relevance
“…To achieve this, Christodoulou and Deligianni (2010) used neurofuzzy decision framework. Other technique found in literature is in the work by Park et al (2008), who use log-linear ROCOF and the power law process to model the failure rate and estimate the economically optimal replacement time of the individual pipes.…”
mentioning
confidence: 99%
“…To achieve this, Christodoulou and Deligianni (2010) used neurofuzzy decision framework. Other technique found in literature is in the work by Park et al (2008), who use log-linear ROCOF and the power law process to model the failure rate and estimate the economically optimal replacement time of the individual pipes.…”
mentioning
confidence: 99%
“…The pipe based models work with homogenous pipes (same environmental and network features) and applies ROCOF function to each of them. However, at least five historical failures per pipes are necessary to estimate the ROCOF functions [17]. So many known failures rarely happen in practice.…”
Section: • Mechanistic Modelsmentioning
confidence: 99%
“…Other techniques found in literature include the work by Park et al (2008), and Ekinci and Konak (2009). Park et al (2008) presented and compared applications of a the log-linear ROCOF method and the power law process to model pipe failure rates and to estimate economically optimal replacement times, concluding that the log-linear ROCOF method performed better.…”
Section: State Of Knowledgementioning
confidence: 99%
“…Park et al (2008) presented and compared applications of a the log-linear ROCOF method and the power law process to model pipe failure rates and to estimate economically optimal replacement times, concluding that the log-linear ROCOF method performed better. Furthermore, they concluded that recording each failure time results in better modelling of the failure rate than observing failure numbers in some time intervals.…”
Section: State Of Knowledgementioning
confidence: 99%